Bananas of the Autonomous Region of Bougainville: a catalog of banana diversity seen on the islands of Bougainville and Buka, Papua New Guinea - Sachter-Smith, Gabriel L.; Paofa, J.; Rauka, G.; Sardos, J.; Janssens, S. (2017)
A catalogue of Musa specimens that were collected for addition to the national banana germplasm collection held by NARI.